Scutellaria barbata D. Don Polysaccharides Inhibit High Glucose-Induced Proliferation and Angiogenesis of Retinal Vascular Endothelial Cells - Li W (Dove Medical Press, 2021)
Wenjun Li,1 Hongxia Xiao2 1Department of Ophthalmology, NHC Key Laboratory of Hormones and Development, Tianjin Key Laboratory of Metabolic Diseases, Chu Hsien-I Memorial Hospital & Tianjin Institute of Endocrinology, Tianjin Medical University, Tianjin, 300134, People’s Republic of China; 2Department of Ophthalmology, Jingmen NO.2 People’s Hospital, Jingmen, 448000, People’s Republic of ChinaCorrespondence: Hongxia Xiao Email drhongxia@163.comPurpose: The traditional Chinese medicine Scutellaria barbata D. Don (S. barbata) has been reported to exhibit anti-cancer and anti-inflammation activities. The ethanol extract of S. barbata has been confirmed to attenuate diabetic retinopathy (DR). This study aimed to investigate the effects and underlying mechanisms of the polysaccharides isolated from S. barbata (PSB) on the proliferation and angiogenesis of retinal vascular endothelial cells (RVECs) in DR.Methods: Human RVECs (HRVECs) were cultured in normal glucose (NG, 5.5 mM), mannitol (MA, 30 mM), high glucose (HG, 30 mM) and HG plus 40 μg/mL PSB, respectively. Then, cell proliferation, migration and angiogenesis were evaluated. The cell proliferation was also estimated in the presence of SLIGKV, which was used to induce the phosphorylation of ERK (p-ERK).Results: PSB reduced normal and HG-induced HRVECs cell viability in a concentration-dependent manner. The protein expression of proliferating cell nuclear antigen (PCNA) and proliferating antigen KI67 (Ki67), the migration rate and tube formation ability, which were increased by HG treatment, were significantly decreased by PSB. PSB also inhibited the phosphorylation of Raf, MEK and ERK in HG-stimulated HRVECs. Moreover, the application of SLIGKV recovered cell viability and the expression of p-ERK, PCNA and Ki67, in HG plus PSB-treated cells. Finally, the HG-enhanced expression of VE-cadherin, Frizzed, β-catenin, MMP-2 and MMP-9 was all reversed by PSB.Conclusion: PSB could inhibit HG-induced HRVECs proliferation, migration and neovascularization, and these effects might work through blocking the activation of MEK/ERK pathway and VEGF/VE-cadherin axis.Keywords: Scutellaria barbata, polysaccharides, retinal vascular endothelial cells, diabetic retinopathy